Demographic Spectrum of Oral Squamous Cell Carcinoma in Public Health Care Facility in Karachi Pakistan - Sana Mubarak, Shazia Akbar, Bhunesha Devi, Uzma Tariq, Ambreen Junaid (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: The aim of this study was to evaluate the spread and proportion of oral squamous cell carcinoma in oral lesions. Methods: Patient’s biopsies were collected from january2017 till July2017 from histopathology lab in public health care institute. Two types of specimens either submitted for diagnosis or post-operative analysis of the lesion were reported. The data of oral tissue biopsies was analyzed and cases were sorted on the basis of benign and malignant lesions. The incidence of cancer and benign lesions was reported as; gender, age and site. Results: Moderately differentiated histological subtype of oral squamous cell was found to be most prevailing in the middle age male population and the etiology and site were found to have the direct association. Conclusion: Our study reveals that male patients are more affected with the disease and the age group ranges from young to middle age individuals. The alteration in lifestyle, awareness and strict laws against the consumption of carcinogenic agents is necessary to address the problem. Keywords: Squamous Cell Carcinoma, Benign Lesion, Malignant Lesions, Biopsies